PERAN DINAS KOMUNIKASI DAN INFORMATIKA DALAM MEWUJUDKAN INFORMASI YANG BERETIKA DAN BERTANGGUNG JAWAB DI PROVINSI RIAU - Jhon Carlos Purba; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The hight rate offense in using social media and least of the knowledge of the society about the information that have ethics and responsibility make some problems in the information and communication aspect. In this case, The Official of Communication and informatics in Riau Province, have a role to create the information that have ethics and responsibily. Based on that case, researcher want to hold the research about The Role of the Official Communication and Informatics to Create the Information that have ethics and responsibily in Riau Province. This research aims to know The Role of the Official Communication and Informatics to Create the Information that have ethics and responsibily in Riau Province and the factors that effect The Role of the Official Communication and Informatics to Create the Information that have ethics and responsibily in Riau Province.This research using the concept of Role Theory, which explain some indicators such as informant, facilitator,and Mediator. This research using the Qualitative Approach with Collecting Data Techniques of interview, observation and documentation. This research informan is the Head of Public Infomation at The Official of Communication and informatics, The Employees in field of Public information and society.Based on the research, it can be known that The Role of the Official Communication and Informatics to Create the Information that have ethics and responsibily in Riau Province still not maximum. And the factors that affect is Communication, resources and means and also the funds and budget.Keyword: Role, Communication Ethics, and Organization Development